Identifikasi Penyebab Kerusakan Konstruksi Bangunan Beton Bertulang Pasca Bencana Gempa Bumi - Tanjung, Jafril; Putri, Nilda Tri (Jurnal Bangunan, Konstruksi & Desain, 2023)
Reinforced concrete is a construction that is vulnerable to damage during an earthquake if not done properly. This article focuses on the results of field observations after the earthquake disaster in Lombok and Palu in 2018, with the aim of identifying the type of damage that occurred in reinforced concrete buildings. This identification is important to understand the potential causes of damage and/or collapse in reinforced concrete buildings. The results of field observations show that low concrete quality and lack of standard reinforcement detailing processes are the main factors contributing to the large number of buildings experiencing damage and/or collapse during the earthquake. Poor quality concrete, such as a mismatch in the mix or a lack of strength, can make a structure brittle and unable to withstand excessive earthquake forces. Apart from that, lack of attention to the reinforcement detailing process is also a cause of significant damage. Non-standard reinforcement detailing includes a lack of the required amount of reinforcement in the structure, installation of shear reinforcement that does not meet the requirements, and a lack of shear reinforcement at beam and column connections. Lack of reinforcement in structural connections reduces the strength and stiffness of the structural system, thereby increasing the risk of collapse during an earthquake. The location and method of installing brick walls is also one of the factors causing building damage. Through analysis of the results of these observations, it can be concluded that good quality concrete and the process of detailing reinforcement and brick walls according to standards are very important to reduce damage and increase the resistance of reinforced concrete structures to earthquakes. Proper implementation of structural design specifications and careful monitoring during construction can help reduce the risk of damage caused by earthquakes.